The Role of Epoxyeicosatrienoic Acids in Diabetes Mellitus-Induced Impaired Vascular Relaxation of Aortic Rings in Ovariectomized Sprague-Dawley Rats - Dragan Manojlović; Ana Stupin; Anita Matić; Zrinka Mihaljević; Sanja Novak; Ines Drenjančević (International Journal of Endocrinology)
Aim. The present study was aimed at determining if type 1 diabetes mellitus (DM) affects vascular function and at elucidating the mechanisms mediating vasorelaxation in both nonovariectomized and ovariectomized Sprague-Dawley (SD) rats. Materials and Methods. Eighty female SD rats were divided into four groups: nonovariectomized healthy (non-OVX-CTR) and diabetic (non-OVX-DM) rats and ovariectomized healthy (OVX-CTR) and diabetic (OVX-DM) rats. Bilateral ovariectomy was performed at the age of 5 weeks, and type 1 DM was induced by streptozotocin at the age of 6 weeks. At the age of 12 weeks, acetylcholine-induced relaxation (AChIR) was assessed in aortic rings in the absence/presence of L-NAME, Indomethacin, and MS-PPOH. Aortic tissue mRNA expression of eNOS, iNOS, COX-1, COX-2, thromboxane synthase 1 (TBXAS1), CYP4A1, CYP4A3, and CYP2J3, as well as plasma oxidative stress, was measured. Results. AChIR did not differ in non-OVX-DM rats compared to non-OVX-CTR ones. AChIR was significantly reduced in the OVX-DM group compared to the OVX-CTR group. MS-PPOH did not reduce AChIR in OVX-DM rats as it did in OVX-CTR ones. CYP4a3 mRNA expression in OVX-DM rats was significantly lower compared to that in the OVX-CTR group. Conclusions. Female sex hormones may protect vasorelaxation in type 1 diabetic rats. Type 1 diabetes impairs vasorelaxation in response to ACh in ovariectomized rats (but not in nonovariectomized rats) by affecting vasorelaxation pathways mediated by EETs.